Embryonal Rhabdomyosarcoma: Rare Case Reports with Middle Ear Location - Runky Pebranka; Salmiah Agus; Yessy Setiawati (Indonesian Journal of Rheumatology, 2023)
Background: Patients with embryonal rhabdomyosarcoma (EMRS) are dominated by boys. The peak incidence occurs in the small age group from one year to 4 years. Approximately 35% of all pediatric RMS occur in the head and neck. Case presentation: A 3-year-old male patient came to the ear, nose, throat-head neck (ENT-HNS) polyclinic at Dr. M. Djamil General Hospital Padang on February 25th, 2021, with complaints of a lump appearing in his right ear canal for 4 months. The patient also complained of slanting on the right side of his face and pain in his right ear since 2 weeks ago. History of bleeding from the ear 1 week ago. On the examination of House-Brackmann, the patient obtained a category House-Brackmann V. Histopathological results, microscopically visible pieces of tissue with part of the surface covered with keratinized squamous epithelium, part of the surface not keratinized. There are dense groups consisting of a proliferation of cells with round, oval nuclei, small to medium size, little cytoplasm, some cells with pleomorphic nuclei, hyperchromatic, irregular nuclear membranes, lots of eosinophilic cytoplasms, with the appearance of "tadpole”, atypical mitoses may be found. The underlying tissue stroma appears myxoid. Among them, fibrotic connective tissue septa containing partially hyperemic capillaries are visible. Necrotic areas and clusters of PMN leukocytes and cellular debris were also seen. This description is consistent with EMRS. Conclusion: The patient was diagnosed with right middle ear EMRS stage III with right peripheral facial nerve paresis House-Brackmann V.